The Existing Relationship Between the Methodology Used by a Cience Teacher and the Motivation Displayed by the Students of a 9th Grade Group - Alvarado Arguedas, Andrea (2011)
In the education system, Science has always been considered a traditional lectures subject inside the curriculum institutions. This conception has provoked serious problems in the teaching process because students have not developed a proper interest and motivation that fulfill their learning needs provoking effects on the scientific and technological development of the country. In order to take note of the situation, a research was conducted at a private day institution in the 01 circuit of Heredia province. The information was gathered through different instruments: three six-lesson observations, a teacher interview, a students' questionnnaire about their opinion on Science class methodology and the use of teaching resources. Finally, amotivational scale was given to students to measure and determine their interest on the subject and their lived experiences as part of their learning process.